Single-mode microwave heating for food science research: Understanding specific microwave effects and reliability concerns - Xidong Jiao; Haifeng Diao; Tianyi Liu; Bowen Yan; Xiangwei Tang; Daming Fan (Food Physics)
Microwave heating is one of the most significant food-related physical-field processing technologies, possessing wide application potential in the food industry and for scientific research. This study explores microwave heating characteristics by conducting Multiphysics numerical simulations within a single-mode microwave system, emphasizing the impact of solvent type and volume on the heating rate, temperature profile, and distribution of the electric field and power dissipation density. In addition, the study examined the microwave-induced aggregation behavior of myofibrillar proteins (MPs) in diverse monovalent salt solvents by employing an established heating protocol. Results indicate that both the volume and type of solvent influence the microwave heating rate considerably. Specifically, volumes of 2 and 3 mL exhibited significantly higher rates than those of 1 and 4 mL under the test conditions, and these alterations were relatively consistent with the observed distributions of the electric field and power dissipation density. Simulations and measurements disclosed notable temperature gradients within the heating system, which were also affected by the solvent volume and type. Abnormal convection led to increased temperatures in the upper solution layers, and this abnormal convection-induced higher temperature could affect the experimental outcomes in scientific research. Using the aggregation behavior of MPs as an example, we also demonstrated the crucial importance of selecting appropriate heating volumes in single-mode microwave systems. These findings offer a theoretical basis for comprehending microwave-heating processes in single-mode reactors and clarify the common microwave-specific effects encountered in laboratory settings.